P167 Pilot feasibility trial of targeted sexual risk reduction interventions within sexual health settings in england – the santé project. (8th June 2017) - King, Carina; Llewellyn, Carrie; Anstee, Sydney; Clark, Laura; Bailey, Julia; Pollard, Alex; Abraham, Charles; Burns, Fiona; Rodger, Alison; Copas, Andrew; Shahmanesh, Maryam; Gilson, Richard
Abstract : Introduction: There is evidence from RCTs that brief behavioural interventions can have modest but valuable impacts on sexual risk behaviours and STIs in young people and men who have sex with men (MSM). Implementing these nationally could reduce STIs, but has not yet been done. Santé aims to adapt and pilot a package of evidence-based risk reduction interventions, and assess the feasibility of conducting a large-scale effectiveness trial. Methods: Following a systematic literature review, mixed-methods evaluation of existing practice, and patient and provider preference, a process of Intervention Mapping was used to adapt effective interventions and create an intervention package for MSM and young people. Triage algorithms were developed using routine surveillance data. A pilot cluster trial is running in eight sexual health clinics. Quantitative process data and qualitative interviews with patients and providers will assess feasibility. Results: The intervention package is a triage algorithm which directs patients into a low-intensity digital intervention or high-intensity one-to-one behaviour change consultation. No identified digital interventions were available for piloting; therefore, patients are directed to suitable health promotion websites. An intervention manual incorporating a Five Step Pathway was developed for the one-to-one consultation, detailing the behaviour change elements. Preliminary pilot results will be available in June 2017. Discussion: The pilot will identify issues that need addressing to make a large trial feasible. Although intended to be deliverable within existing clinic resources, current service changes threaten the viability of such innovations. Further adaptation and development of digital resources will be needed prior to implementation.